HUBUNGAN ANTARA TINGKAT STRES DENGAN MEKANISME KOPING PADA MAHASISWA KEPERAWATAN MENGHADAPI PRAKTEK BELAJAR LAPANGAN DI RUMAH SAKIT - Suminarsis, Tyas Ardi; Sudaryanto, Agus (Universitas Muhammadiyah Surakarta, 2009)
Nursing is a professional service that integral part of medichine service. Clinic practice nursing is a transformation to be a professional nurse that give an opportunity for adaptation of her job to do the nursing care and implementation the professional skills. Stress can happen in anywhere and whoever, include a student. Student who has difficulty adapt is separate stressor will pursue learning process to teach causing influences learning process. Management stress done by nursing student in facing stressor in area of using practice working more using refreshing technique up to 75.3%, it caused by the technique more cheaper and can be done with others. Education factor Treatment, family and development duty of contribution to process copping student and will have an effect on the appearance academic. Knowing the relation between stress level with coping mechanismof the clinic nursing student’s clinic practice in the hospital. Descriptive correlative research method with sectional approach, executed in dr, moewardi Hospital and Muhammadiyah University of Surakarta. Research on 22 June until 1 July 2009. the population students of PSIK UMS programme A (regular) grade 2007, executes practicing field learning in hospital are 87. The sampling method is proportional random sampling count 47 samples. Variable dependent: copping mechanism, Variable independent: the rate of stress of students at the firs time of learning practice working. Analyzed applies with statistic Chi Square test (X2 ). The result of the examination relation between stress level student with copping mechanism is value X2 = 19.950 with p-value = 0.001. Concluded there is correlation between stress level student with copping mechanism at UMS’s students that executes practicing working in hospital. Excelsior level of stress student, increasingly copping mechanism UMS’s student are executes practicing learning at hospital tends is maladaptive.